'Working behind the scenes' An ethical view of mental health nursing and first-episode psychosis. (August 2013) - Moe, Cathrine; Kvig, Erling I; Brinchmann, Beate; Brinchmann, Berit S
The aim of this study was to explore and reflect upon mental health nursing and first-episode psychosis. Seven multidisciplinary focus group interviews were conducted, and data analysis was influenced by a grounded theory approach. The core category was found to be a process named 'working behind the scenes'. It is presented along with three subcategories: 'keeping the patient in mind', 'invisible care' and 'invisible network contact'. Findings are illuminated with the ethical principles of respect for autonomy and paternalism. Nursing care is dynamic, and clinical work moves along continuums between autonomy and paternalism and between ethical reflective and non-reflective practice. 'Working behind the scenes' is considered to be in a paternalistic area, containing an ethical reflection. Treating and caring for individuals experiencing first-episode psychosis demands an ethical awareness and great vigilance by nurses. The study is a contribution to reflection upon everyday nursing practice, and the conclusion concerns the importance of making invisible work visible.